RAIL-MATH: MEDIA PEMBELAJARAN BERORIENTASI CULTURALLY RESPONSIVE TEACHING SEBAGAI INOVASI PEMBELAJARAN SPLDV KELAS VIII - Ifta Khamidatu Zufa; Eko Andy Purnomo; Venissa Dian Mawarsari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Based on the results of observation activities on eighth grade students at Alhuda Junior High School Semarang, it was found that the level of students' problem-solving abilities, especially in SPLDV material, was still minimal. The main cause was that the learning media used by teachers tended to be conventional and did not sufficiently integrate mathematical concepts into students' daily realities. This study aimed to develop Rail-Math interactive learning media oriented to Culturally Responsive Teaching (CRT) on SPLDV material while assessing its level of validity in supporting students' mathematical problem-solving abilities. Rail-Math media was developed in the form of a digital module presented through a flipbook format to increase students' active involvement in learning. This study used the Research and Development (R&D) method with the stages of defining, designing, and developing. Product validation was carried out by material experts and media experts through a Likert-sized quantitative instrument, supplemented by qualitative input. The validation results showed an average score of 3.63 for material experts and 3.61 for media experts, included in the very valid category. Thus, Rail-Math was declared worthy of being used as an innovative media that is relevant to SPLDV material and has the potential to improve students' mathematical problem-solving abilities.